Cross Sections for the \(^{nat}\)Zr\((p,xn)^{89,90}\)Nb Reactions Induced by 27.7 MeV Protons - Khue, Pham Duc; Do, Nguyen Van; Anh, Le Tuan (Communications in Physics, 2015)
The cross-sections for the formation of \(^{89}\)Nb and  \(^{90}\)Nb radionuclides in proton induced nuclear reactions on zirconium  were measured by using the well known activation method. The natural  zirconium (\(^{nat}\)Zr) target and copper (\(^{nat}\)Cu) monitor foils were  irradiated by 27.7 MeV proton beam at the MC50 Cyclotron of the Korea  Institute of Radiological and Medical Science (KIRAMS), Korea. The induced  gamma activities of the reaction products were measured by a coaxial high  purity germanium (HPGe) detector coupled to a PC-based multichannel  analyzer. The obtained cross sections for each nuclide are compared with  those existing in literature and with the theoretical cross sections  calculated by the TALYS - 1.4 code.